Comparison between Alterations in some Hematological and Biochemical Parameters in COVID-19 and non-COVID-19 Patients Albaida, Libya - Hussein, Marium M. (Scientific Journal for Faculty of Science-Sirte University, 2022)
The COVID-19 outbreak has resulted in an unexpected health crisis all around the world. It was on March 11, 2020, when the WHO declared it as a pandemic. Ever since an exponential increase in the disease has been seen. The coronavirus disease 2019 or COVID-19 is a beta-coronavirus that has been closely related to the SARS-CoV-2 by means of genetic sequencing methods. This disease is associated with alterations in the complete blood picture and coagulopathies. In this present study, the role of hematological and biochemical parameters of blood in predicting COVID-19 infection w investigated, as these blood analyzes are considered a vital indicator for confirmation of infection. The present work was designed to diagnose COVID- 19 with five basic blood tests: white blood cells (WBC), lymphocytes (LYM), neutrophils (NEUT), platelets (PLT), and clotting factor D–dimer as well as the diagnosis of COVID-19 associated tests. Biochemical blood C-reactive protein (CRP), serum ferritin (FRR), and Lactic dehydrogenase (LDH). It was noted that the hematological and biochemical blood tests included in this study were capable of diagnosing COVID-19, due to their increase or decrease in the normal rates, according to what was shown in the results. N The diagnosis of COVID-19 using blood and blood biochemical tests in people who show some mild clinical symptoms, high and low levels of these parameters have been closely associated with COVID-19 infection and may also serve as biomarkers to predict infection.